High-fluidity self-compacting backfill grouting material for buried pipe and its application in ground source heat pump
Patent Information
- Application Number
- CN202611182455.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-30
AI Technical Summary
在200米以深的完整岩体段,依靠高流动性灌浆料的自重压力即可获得满意的渗透和填充效果;但在100~200米的裂隙密集段,仅靠自重产生的渗透驱动力往往不足,无法将浆液有效推入微裂隙深处,最终仍会在该关键段留下不良接触界面,成为限制地埋管换热效率提升的瓶颈
[0045]1、本发明突破常规回填仅依赖重力静压的局限,首创井下变频振冲辅助灌浆工法,利用振动剪切稀化效应驱动浆液主动渗入深层闭合裂隙;同时通过频率无级调节适配100~200m过渡带裂隙随深度衰减的地质规律,实现全孔段浆-岩界面化学结合与低热阻均匀回填,显著提升地源热泵系统的长期换热稳定性。
Smart Images

Figure QLYQS_1 
Figure QLYQS_8
Abstract
Description
Technical Field
[0001] This invention relates to the field of ground source heat pump construction technology, specifically to a high-flowability, self-compacting ground-buried pipe backfill grout and its application in ground source heat pumps. Background Technology
[0002] Ground source heat pump systems utilize underground constant-temperature layers for heat exchange. Vertical buried pipe heat exchangers require backfill material to be injected into the annular space between the borehole and the buried pipe. The backfill material plays a crucial role in bonding the buried pipe to the surrounding soil, protecting the pipe, blocking groundwater, and transferring heat. Currently, commonly used backfill materials include original soil, bentonite-sand mixtures, and ordinary cement-based grout. Original soil and bentonite mixtures have low thermal conductivity and are prone to forming cracks and cavities around the buried pipe, significantly increasing thermal resistance. While ordinary cement-based grout improves thermal conductivity, it often only possesses basic fluidity and filling properties, lacking the ability to penetrate and wet the disturbed soil around the borehole wall. In actual geological formations, the drilling process leads to the formation of numerous micro-cracks and loose zones around the borehole wall. Ordinary backfill grout cannot effectively penetrate these micro-cracks, ultimately leaving a poor contact interface between the buried pipe, backfill material, and soil, severely hindering heat conduction and limiting further improvements in the energy efficiency ratio of the heat pump system.
[0003] While existing technologies include methods to improve contact by using expansion agents to induce micro-expansion in grouting materials, their expansion effect is only effective for larger cavities and still lacks the ability to actively penetrate into the micro-cracks of the surrounding soil.
[0004] It should be noted that, in existing technologies, layered silicate minerals (such as bentonite) are generally considered to have strong hydrophilic swelling properties. Adding them to cement grout increases the grout's viscosity and reduces its fluidity. Furthermore, their expansion primarily serves to block pores rather than promote outward permeation of the grout. Therefore, technicians would have no incentive to add large quantities of such mineral materials when faced with tasks requiring the grout to actively infiltrate the soil.
[0005] Furthermore, the geological conditions traversed by vertical buried pipe boreholes for ground source heat pumps vary significantly with depth. A general geological pattern is that the shallower the depth, the stronger the weathering and unloading effect on the rock mass, and the higher the degree of microfracture development around the borehole wall; the deeper the depth, the more intact the surrounding rock, and the significantly fewer the number of microfractures. Taking typical granite or sandstone strata as an example, the loosened zone and microfracture network caused by borehole disturbance are most dense around 100 meters, due to the transition zone between weathered and fresh rock mass; while at depths above 200 meters, the rock mass is more intact, and fractures are relatively sparse after borehole formation. This difference in fracture distribution places different demands on the permeability of the backfill grout. In intact rock sections deeper than 200 meters, satisfactory penetration and filling effects can be achieved by relying on the self-weight pressure of highly fluid grout. However, in densely fractured sections of 100 to 200 meters, the penetration driving force generated by self-weight alone is often insufficient to effectively push the grout into the depths of micro-fractures. Ultimately, poor contact interfaces will still be left in this critical section, becoming a bottleneck that limits the improvement of heat exchange efficiency of buried pipes.
[0006] Therefore, developing a high-permeability self-compacting backfill grout that can actively penetrate into soil fissures and greatly reduce contact thermal resistance, and proposing effective auxiliary infiltration construction methods for densely fissure sections of 100-200 meters, has become an urgent need to improve the performance of ground source heat pump systems. Summary of the Invention
[0007] This invention addresses the shortcomings of existing technologies by providing a highly fluid, self-compacting grout for backfilling buried pipes and its application in ground source heat pumps. The technical solution is as follows:
[0008] In one aspect, the present invention provides a highly fluid self-compacting backfill grout for buried pipes, comprising cementitious components, aggregates, water-reducing agents, permeability-enhancing materials, permeable masterbatch, and water;
[0009] The cementitious components include aluminate cement, slag powder, fly ash, and silica fume;
[0010] The aforementioned permeability-enhancing material enables the grout to actively penetrate into sandy soil media with a particle size of 0.5~2mm while maintaining a fluidity of ≥320mm, achieving a penetration depth of ≥5.0mm in 24 hours.
[0011] The permeation masterbatch is a composite of soluble silicates, fluorosilicates and active silica;
[0012] After hardening, the grouting material forms a chemical crystal bond with the soil in the permeable area, with a 28-day compressive strength ≥25MPa and a thermal conductivity ≥2.2W / (m·K).
[0013] Furthermore, the permeation-enhancing material is ionic liquid-lithium composite modified bentonite, which is prepared by organic-lithium composite intercalation modification of sodium-based bentonite using long-chain alkyl imidazole ionic liquid as organic intercalating agent and soluble lithium salt as secondary ion exchange stabilizer.
[0014] The cation of the ionic liquid contains a long-chain alkyl group with ≥12 carbon atoms, and the anion is a halide ion.
[0015] Furthermore, the ionic liquid is at least one of 1-hexadecyl-3-methylimidazolium chloride and 1-octadecyl-3-methylimidazolium bromide.
[0016] Preferably, the high-flowability self-compacting backfill grout for buried pipes comprises, by weight: 30-50 parts aluminate cement, 10-25 parts slag powder, 5-15 parts fly ash, 2-6 parts silica fume, 4-10 parts permeability promoting material, 40-65 parts aggregate, 1-5 parts permeable masterbatch, and 0.5-2 parts water-reducing agent; the water-cement ratio is 0.28-0.38.
[0017] Furthermore, the permeation masterbatch is composed of sodium silicate, magnesium fluorosilicate, and active silica in a weight ratio of 1:(0.3~0.8):(0.2~0.5).
[0018] Preferably, the aggregate is quartz sand; more preferably, it is composed of quartz sand with two particle sizes of 40-70 mesh and 70-120 mesh mixed in a weight ratio of (3-5):1.
[0019] Preferably, the water-reducing agent is a polycarboxylate water-reducing agent, and the dosage is 0.5 to 2 parts.
[0020] Furthermore, the preparation method of the ionic liquid-lithium composite modified bentonite includes the following steps:
[0021] 1) Mix sodium-based bentonite with water to form a suspension, and heat to 70~80℃;
[0022] 2) Add a long-chain alkylimidazolium ionic liquid with a cation exchange capacity of 0.6 to 1.0 times that of sodium-based bentonite to the reaction under stirring;
[0023] 3) Add soluble lithium salt with a cation exchange capacity of 0.1 to 0.4 times that of sodium-based bentonite to carry out the reaction;
[0024] 4) Wash, dry, and pulverize the product obtained after the reaction is complete to obtain the final product.
[0025] In another aspect, this invention provides a new application: the application of the aforementioned high-flowability self-compacting buried pipe backfill grout in a ground source heat pump. The high-flowability self-compacting buried pipe backfill grout is prepared as a grouting material and injected into the annular space of the vertical buried pipe borehole of the ground source heat pump using a grouting pump. Relying on its own weight, the grout self-levels and fills the space densely. Simultaneously, under the synergistic effect of the permeability regulating components and the permeability masterbatch, it seeps into the micro-fractures in the soil surrounding the borehole, where a secondary crystallization reaction occurs, forming a chemically interlocked integral backfill body with the soil.
[0026] Furthermore, for fractured borehole sections with depths ranging from 100m to 200m, the penetration depth relying solely on the weight pressure of the grout is limited. This invention proposes simultaneously lowering a downhole variable frequency vibratory compactor during backfilling of such sections for vibration-assisted grouting. The penetration depth is actively controlled by adjusting the frequency and vibration duration. The downhole variable frequency vibratory compactor is an electric or hydraulic vibration device that can be lowered to deep boreholes via a wire rope, with a working depth of up to 200m. Its construction parameters are determined based on the following variable frequency vibratory compaction-control equation:
[0027] ;
[0028] Where: L is the vibration-assisted penetration depth (m); Let L0 be the depth of penetration by self-weight without vibration at the vibration-assisted penetration depth; at a certain construction depth z, without any vibration assistance, the maximum depth to which the grout can naturally penetrate into the micro-cracks of the surrounding soil by its own weight and capillary action is denoted as L0. The enhancement factor is dimensionless; f is the operating frequency (Hz) of the downhole variable frequency vibratory impactor. z is the vibration retention time (s); z is the construction depth (m); For reference depth, we take 1m.
[0029] In this invention, the downhole variable frequency vibratory compactor can not only complete the task of drilling, but also further enhance the exchange of grout material with the surrounding soil during backfilling, and can also compact the grout material.
[0030] The vibration frequency of the downhole variable frequency vibratory compactor can be steplessly adjusted within the range of 10~80Hz. Before construction, a typical depth is selected on-site for calibration: at a known construction depth z, the downhole variable frequency vibratory compactor is turned off, and L0 is measured under vibration-free conditions. Then, the frequency f and the vibration dwell time t are set. v The vibration-assisted penetration depth L after actual vibration was measured, and the enhancement coefficient k was calculated by back-calculation. f The enhancement coefficient k f Once calibrated, it is applicable to the entire borehole section.
[0031] During construction, in sections with dense cracks, the current construction depth z and the required penetration depth are considered. Calculate the required vibration dwell time using the following formula. :
[0032] ;
[0033] In the formula, z0 = 1m. The operating frequency f and the dwell time of the downhole variable frequency vibratory actuator are adjusted. This allows for uniform and deep penetration at any depth.
[0034] In this invention, the variable frequency vibration-control equation is applied in a fracture development transition zone of 100-200m. Rock mass integrity improves nonlinearly with depth, and the decrease in permeability is the dominant factor determining the permeation depth. The depth term z in the equation reflects the constraint effect on permeability caused by the increasing depth, the tendency of the rock mass to become more intact, and the decrease in fracture density and aperture. This constraint effect is generally much greater than the driving gain brought about by the increase in hydrostatic pressure in the 100-200m fracture development transition zone; therefore, the overall permeation depth shows a decreasing trend with increasing depth.
[0035] Furthermore, a phased construction and graded material usage strategy is adopted:
[0036] In the borehole section with a drilling depth of 0~100m, conventional backfill grouting material is used for filling by its own weight.
[0037] In borehole sections with a drilling depth of 100-200m, the high-flowability self-compacting grouting material is used for backfilling, and the grouting is assisted by the downhole variable frequency vibratory compactor.
[0038] The conventional backfill grouting materials include pure bentonite grout, bentonite-sand mixture, ordinary bentonite-cement grout, pure cement paste, cement mortar, graphite-cement based grouting material, quartz powder-cement based grouting material, silicon carbide-cement based grouting material, volcanic ash-cement based grouting material, granulated blast furnace slag-cement based grouting material, etc.
[0039] It should be noted that the conventional backfill grout is a bentonite-based or ordinary cement-based mixture that only has a passive filling function and forms a physical contact interface with the surrounding soil, resulting in gap thermal resistance. Its advantage is that the cost and construction cost are very low.
[0040] In this invention, a variable frequency vibratory compaction-assisted backfilling method is employed, overcoming the limitations of static pressure grouting and achieving active filling of deep fractures. Unlike traditional ground source heat pump construction, which either does not use vibratory compactors or uses vibratory compactors designed for foundation drilling in the drilling construction mode of this invention (where even with this method, the final backfilling relies entirely on the inherent gravity static pressure), this invention introduces a downhole variable frequency vibratory compactor into the backfilling grouting process. Its core advantages are:
[0041] ① During conventional static pressure grouting, the grout slowly seeps into microfractures under its own weight and water head, and is easily stagnated due to capillary resistance and air blockage. This invention applies controllable high-frequency, low-amplitude vibration through a downhole variable frequency vibratory compactor, which significantly reduces the apparent viscosity of the thixotropic grout (shear thinning) and lowers the seepage resistance, thereby transforming passive static pressure into active dynamic seepage, enabling the grout to effectively enter deep closed microfractures that are inaccessible by conventional methods.
[0042] ② In this invention, although there are many weathering fissures in the shallow layer (0~100m), the pore size is relatively large, and static pressure is sufficient; while in the deep layer (100~200m), the fissures are narrow and the ground stress is high, making dynamic permeability urgently needed. This invention overcomes the shortcomings of traditional constant frequency vibratory vibrators, which cannot change their single frequency with depth. It adopts a 10~80Hz stepless frequency conversion, which can flexibly adjust the excitation frequency according to the real-time hole depth and rock mass wave velocity response, avoiding over-vibration leading to slurry segregation or under-vibration leading to insufficient permeation, thus achieving uniform control of the permeability effect throughout the entire hole section.
[0043] ③ During the vibro-compaction process, the grout is subjected to periodic pulsating pressure within the fissures. This not only removes the stagnant water film and air from the fissures, but also promotes the diffusion of active ions (silicate and fluorosilicate) in the permeation masterbatch into the deeper layers of the rock wall under pressure pulsation. This makes the chemical crystallization anchoring reaction more complete and transforms the physical contact interface into a chemically bonded transition layer, which is significantly better than the passive contact interface formed after conventional grouting.
[0044] Compared with the prior art, the beneficial effects of the present invention are:
[0045] 1. This invention breaks through the limitations of conventional backfilling that relies solely on gravity static pressure. It pioneers a downhole variable frequency vibratory grouting method, which utilizes the vibration shear thinning effect to drive the grout to actively penetrate deep closed fractures. At the same time, by steplessly adjusting the frequency to adapt to the geological law of fracture attenuation with depth in the 100~200m transition zone, it achieves chemical bonding of the grout-rock interface and uniform backfilling with low thermal resistance throughout the entire borehole section, significantly improving the long-term heat exchange stability of the ground source heat pump system.
[0046] 2. This invention uses ionic liquid-lithium composite modified bentonite as a permeation-promoting material, overcoming the prejudice of traditional bentonite's thickening and pore-blocking properties. Under the premise of a flowability ≥320mm, it achieves a penetration depth of ≥5.0mm into sandy soil media within 24 hours, filling the technical gap that backfill grout cannot actively repair pore wall disturbance cracks.
[0047] 3. After penetrating into the fissures, the permeable masterbatch of the present invention reacts with calcium and aluminum ions in the soil to generate insoluble crystals (such as hydrated calcium silicate and calcium fluorosilicate), transforming physical contact into chemical bonding. The interfacial pull-out strength is ≥1.5MPa and the failure occurs inside the soil, which helps to solve the problem of poor contact.
[0048] 4. The backfill material produced by this invention has a 28-day compressive strength ≥25MPa and a thermal conductivity ≥2.2W / (m·K), which meets the requirements for efficient heat exchange while ensuring the structural bearing capacity.
[0049] 5. Compared with traditional quaternary ammonium salt modified bentonite, the present invention retains a penetration depth of ≥95% after soaking in hot water at 60℃ for 90 days (far superior to the 78% of the comparative example), making it very suitable for the long-term hot and cold alternation operation environment of ground source heat pumps.
[0050] 6. For the critical fracture section of 100~200m, a variable frequency vibratory compaction-assisted construction method and precise control equations are proposed. By adjusting the frequency and vibration time, the vibration time is saved compared with the traditional constant frequency vibratory compaction, avoiding the temperature rise and strength deterioration of the slurry caused by long-term vibration, and realizing uniform and high-quality backfilling of the entire hole section. Detailed Implementation
[0051] The present invention will be described in detail below with reference to specific embodiments. These embodiments are merely some, not all, implementations of the present invention. All other implementations obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0052] Example 1
[0053] Weigh out the following materials: CA-50 aluminate cement: 40 kg; S95 grade slag powder: 20 kg; Grade I fly ash: 10 kg; silica fume: 4 kg; ionic liquid-lithium composite modified bentonite: 4.5 kg; quartz sand (40~70 mesh quartz sand: 70~120 mesh quartz sand mass ratio = 4:1): 56.5 kg; penetrating masterbatch (sodium silicate: magnesium fluorosilicate: active silica mass ratio = 1:0.6:0.4): 3 kg; polycarboxylate superplasticizer powder: 0.9 kg; defoamer: 0.2 kg. Mix the above materials evenly, add water at a water-cement ratio of 0.33 and stir for 3 minutes to obtain the grouting material. The water-cement ratio is the mass of mixing water to the total mass of cementitious materials. In this example, the cementitious materials are aluminate cement, slag powder, fly ash, and silica fume.
[0054] One method for preparing ionic liquid-lithium composite modified bentonite (using 1-hexadecyl-3-methylimidazolium chloride) is as follows:
[0055] 1000g of natural sodium-based bentonite with 92% montmorillonite content and a cation exchange capacity (CEC) of 90 mmol / 100g was added to 20L of deionized water, stirred and dispersed, and heated to 75℃. While stirring, 2L of an aqueous solution containing 155g of 1-hexadecyl-3-methylimidazolium chloride (CAS 61546-01-8) was added dropwise, and the reaction was allowed to proceed for 3 hours. Then, 8.4g of lithium carbonate was added, and the pH was adjusted to 6.5±0.1 with 10% citric acid solution, and the reaction was continued for 2 hours. The mixture was ultrasonically dispersed (40kHz, 300W) for 30 minutes, centrifuged and washed until no chloride ions were detected in the filtrate when tested with silver nitrate. The filtrate was dried at 80℃ and then air-jet pulverized to D50=4.2μm to obtain the ionic liquid-lithium composite modified bentonite.
[0056] Performance testing methods:
[0057] Flowability and V-shaped funnel outflow time: Refer to GB / T 50448-2015 "Technical Specification for Application of Cement-based Grouting Materials".
[0058] Penetration depth: Fill a transparent penetration cylinder with standard quartz sand (wet sand medium) with a particle size of 0.5~2.0mm and a moisture content of 8%, maintain the relative density of the wet sand medium at 70%, and inject grout to a height of 200mm at the top. After 24 hours, measure the vertical distance of the grout penetrating into the sand body and take the average value of 3 measuring points.
[0059] Interface pull-out strength: The grout was poured onto a pre-cracked silty clay simulated soil (soil cohesion of about 60 kPa, internal friction angle of 22°), and after curing for 28 days, it was directly pulled out, and the failure load and failure mode were recorded.
[0060] Thermal conductivity: determined using the transient hot wire method, according to ASTM D5334.
[0061] Long-term thermal stability: The specimen was immersed in water at 60℃ for 90 days, and the penetration depth retention rate and thermal conductivity retention rate were tested periodically.
[0062] Performance test results:
[0063] The initial flowability was 355 mm, the 60-minute flowability was 335 mm, and the V-shaped funnel outflow time was 7 seconds. The 24-hour penetration depth in wet sand media with a particle size of 0.5~2 mm was 8.5 mm. The 28-day compressive strength was 28.0 MPa, and the thermal conductivity was 2.32 W / (m·K). The interfacial pull-out strength was 1.58 MPa, and failure occurred within the silty clay. When the grouting material of this embodiment was applied to a ground source heat pump project, the equivalent thermal conductivity of the soil and rock was increased by 22% compared to traditional bentonite backfill drilling, and the COP of the heat pump unit was increased by 12%.
[0064] Example 2
[0065] The preparation method of the ionic liquid-lithium composite modified bentonite (using 1-octadecyl-3-methylimidazolium bromide) in this example differs from that in Example 1 only in that 170g of 1-octadecyl-3-methylimidazolium bromide (CAS No. 379231-56-8) is used instead of 155g of 1-hexadecyl-3-methylimidazolium chloride in Example 1. The remaining steps are the same as in Preparation Example 1.
[0066] In this example, the ionic liquid-lithium composite modified bentonite used in the grouting material was prepared by the above method, and the formulation amount was 5.0 kg; the water-cement ratio was adjusted to 0.34, and the rest was the same as in Example 1.
[0067] Performance test results for this example:
[0068] Initial flowability 350 mm, 24-hour penetration depth 8.2 mm, 28-day compressive strength 27.5 MPa, thermal conductivity 2.28 W / (m·K), interfacial pull-out strength 1.52 MPa, and internal soil failure.
[0069] Example 3 (non-permeable masterbatch)
[0070] The penetrating masterbatch was removed from the formulation of Example 1. The resulting grout had a flowability of 360 mm and a penetration depth of 7.8 mm after 24 hours, but the interfacial pull-out strength was only 0.68 MPa, indicating failure due to interfacial separation.
[0071] As can be seen from the above, the permeation masterbatch plays a key role in forming chemical anchoring.
[0072] Example 4
[0073] The aluminate cement in Example 1 was replaced with an equal amount of P·O 42.5 ordinary Portland cement, and the water-cement ratio was adjusted to 0.38 to obtain similar fluidity. The resulting grout had an initial fluidity of 330 mm, but a penetration depth of only 3.5 mm after 24 hours, a compressive strength of 35.2 MPa after 28 days, a thermal conductivity of 1.8 W / (m·K), and an interfacial pull-out strength of 0.52 MPa.
[0074] Comparative Example 1
[0075] Compared with Example 1, in this example, 98g of 1-butyl-3-methylimidazolium chloride (CAS No. 79917-90-1) is used to replace 155g of 1-hexadecyl-3-methylimidazolium chloride in the raw materials of the grouting material, and the remaining steps are the same as in Example 1.
[0076] The final measured contact angle was only 65°, the initial flow rate was 310 mm, and the 24-hour penetration depth was 2.2 mm, failing to meet the requirement of 5.0 mm.
[0077] Therefore, it can be seen that in the system of the present invention, the use of short-chain ionic liquid modification will lead to the failure of permeation promotion.
[0078] Comparative Example 2
[0079] Compared with Example 1, in this example, 196g of 1-hexadecyl-3-methylimidazolium hexafluorophosphate (CAS No. 219947-95-2) is used instead of 155g of 1-hexadecyl-3-methylimidazolium chloride in the raw materials of the grouting material, and the remaining steps are the same as in Example 1.
[0080] The resulting grout emitted a pungent odor during mixing, and tests revealed the formation of trace amounts of HF, with the pH dropping below 10. The grout's 28-day compressive strength was only 18 MPa, and it exhibited significant corrosion to steel pipes.
[0081] Comparative Example 3
[0082] Compared to Example 1, the raw materials for this grouting material were the same as in Example 1. In this example, 5.5 kg of commercially available octadecyltrimethylammonium chloride modified bentonite (D50=8μm; Zhejiang Huatai New Materials, DK4 type) replaced the 4.5 kg of ionic liquid-lithium composite modified bentonite. The initial flowability of the resulting grouting material was 340 mm, and the penetration depth was 6.0 mm after 24 hours. However, after soaking in water at 60℃ for 90 days, the penetration depth retention rate was only 78%, and the thermal conductivity retention rate was 89%. In contrast, Example 1, under the same conditions, achieved a penetration depth retention rate of 96% and a thermal conductivity retention rate of 98.5%. This demonstrates that ionic liquid modified bentonite has a significant advantage in long-term thermal stability.
[0083] As can be seen from the above embodiments and comparative examples, only by using ionic liquids with carbon chain length ≥12 and halogen anions to intercalate and modify bentonite, and combining it with lithium ion stabilization treatment, and then using it in the specific aluminate cement cementitious system of this invention, can a buried pipe backfill grout material with ultra-high permeability, self-compacting properties, interfacial chemical anchoring, and long-term stability be achieved.
[0084] Example 5
[0085] The grouting material from Example 1 was used for construction, and the grouting method assisted by the downhole frequency converter vibratory compactor is as follows:
[0086] For fractured borehole sections with depths of 100m to 200m, downhole variable frequency vibratory compactors are used to assist grouting. At a borehole depth of 150m, L0 = 0.3, L target =0.8, k is calibrated f =0.15, set f=40Hz, then the calculated t vThe requirement can be met in approximately 25 seconds. This method relies entirely on adjusting the frequency to control the cumulative number of shear cycles, accelerating grout penetration. It does not depend on the fixed parameter of vibratory compactor amplitude, and its construction flexibility and penetration effect are significantly better than the traditional constant frequency vibratory compaction assisted process.
[0087] Comparative Example 4
[0088] During the construction of a ground source heat pump in a geological site in Hebei Province (the same geological site as in Example 5, and part of the same engineering project; various construction methods were used flexibly to expedite the work), conventional constant-frequency vibratory compactors were used to assist grouting at a depth of 150m in adjacent boreholes of adjacent plots. The grout formula was exactly the same as in Example 1. The fixed operating frequency of the constant-frequency vibratory compactor was 40Hz (non-adjustable). During construction, the vibratory compactor continuously vibrated at 150m, and the change in grout penetration depth over time was recorded until the penetration depth reached the target value of 0.8m. The actual measured required vibration retention time was as long as 95s, far exceeding the 25s of Example 5 and also far exceeding the conventional 30-60s vibration retention window; if the conventional 60s vibration retention construction was followed, the penetration depth would only be about 0.55-0.65m, which could not meet the design requirements.
[0089] Meanwhile, due to prolonged vibration, the internal temperature of the grout rose significantly, leading to a decrease in the effectiveness of some water-reducing agents, and the 28-day compressive strength dropped to 26.1 MPa. Therefore, it can be seen that conventional constant-frequency processes, because they cannot adjust the frequency according to depth, have low energy utilization efficiency, and their construction efficiency and grouting quality are significantly inferior to those of this invention.
[0090] Comparative Example 5
[0091] During the construction of a ground source heat pump in a geological site in Hebei Province (the same geological conditions as in Example 5, and part of the same engineering project; various construction methods were used flexibly to expedite the work), a simple linear frequency conversion strategy was employed for auxiliary grouting at a depth of 150m in another borehole under the same geological conditions. This strategy pre-sets the frequency to increase linearly with depth: f = 20 + 0.2 × z, i.e., 20Hz at ground level and 50Hz at a depth of 150m. The vibration dwell time was fixed at 60s, and the grout formulation was the same as in Example 1.
[0092] Under this strategy, the measured permeation depth at 150m was only 0.69m, failing to reach the target value of 0.8m. Even extending the vibration time to 90s only increased the permeation depth to 0.76m, still falling short of the target. This may be because the linear frequency conversion strategy leads to insufficient driving force for deep permeation; the frequency setting of the linear frequency conversion may not have generated a resonant permeation-promoting effect within the effective frequency band. In contrast, the control strategy of this invention employs a special vibration field, which helps control the permeation depth and maximize energy utilization in deep underground construction.
[0093] Furthermore, it should be understood that those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.
Claims
1. A high-flowability, self-compacting grouting material for backfilling buried pipes, characterized in that: Includes cementitious components, aggregates, water-reducing agents, permeability-enhancing materials, permeable masterbatch, and water; The cementitious components include aluminate cement, slag powder, fly ash, and silica fume; The aforementioned permeability-enhancing material enables the grout to actively penetrate into sandy soil media with a particle size of 0.5~2mm while maintaining a fluidity of ≥320mm, achieving a penetration depth of ≥5.0mm in 24 hours. The permeation masterbatch is a composite of soluble silicates, fluorosilicates and active silica; After hardening, the grouting material forms a chemical crystal bond with the soil in the permeable area, with a 28-day compressive strength ≥25MPa and a thermal conductivity ≥2.2W / (m·K).
2. The high-flowability self-compacting grouting material for backfilling buried pipes according to claim 1, characterized in that: The permeation-enhancing material is ionic liquid-lithium composite modified bentonite, which is prepared by organic-lithium composite intercalation modification of sodium-based bentonite using long-chain alkyl imidazole ionic liquid as organic intercalating agent and soluble lithium salt as secondary ion exchange stabilizer.
3. The high-flowability self-compacting grouting material for backfilling buried pipes according to claim 2, characterized in that: The ionic liquid is at least one of 1-hexadecyl-3-methylimidazolium chloride and 1-octadecyl-3-methylimidazolium bromide.
4. The high-flowability self-compacting grouting material for backfilling buried pipes according to claim 1, characterized in that, By weight, the high-flowability self-compacting backfill grout for buried pipes comprises: 30-50 parts aluminate cement, 10-25 parts slag powder, 5-15 parts fly ash, 2-6 parts silica fume, 4-10 parts permeability promoting material, 40-65 parts aggregate, 1-5 parts permeable masterbatch, and 0.5-2 parts water-reducing agent. The water-to-binder ratio is 0.28–0.
38.
5. The high-flowability self-compacting grouting material for backfilling buried pipes according to claim 1, characterized in that, The permeation masterbatch is composed of sodium silicate, magnesium fluorosilicate, and active silica in a weight ratio of 1:(0.3~0.8):(0.2~0.5).
6. The high-flowability self-compacting grouting material for backfilling buried pipes according to claim 2, characterized in that, The preparation method of the ionic liquid-lithium composite modified bentonite includes the following steps: 1) Mix sodium-based bentonite with water to form a suspension, and heat to 70~80℃; 2) Add a long-chain alkylimidazolium ionic liquid with a cation exchange capacity of 0.6 to 1.0 times that of sodium-based bentonite to the reaction under stirring; 3) Add soluble lithium salt with a cation exchange capacity of 0.1 to 0.4 times that of sodium-based bentonite to carry out the reaction; 4) Wash, dry, and pulverize the product obtained after the reaction is complete to obtain the final product.
7. The application of high-flowability self-compacting ground-buried pipe backfill grouting as described in any one of claims 1 to 6 in ground source heat pumps, characterized in that: The high-flowability self-compacting ground-buried pipe backfill grout is made into grout material, which is then injected into the annular space of the vertical buried pipe borehole of the ground source heat pump through a grouting pump.
8. The application according to claim 7, characterized in that, In borehole sections with depths of 100m to 200m, downhole variable frequency vibratory compactors are used to assist grouting. The construction parameters of the downhole variable frequency vibratory compactors are determined based on the variable frequency vibratory compaction control equation to ensure that the penetration depth reaches the target value. ; In the formula: L is the vibration-assisted penetration depth; This is the depth of penetration by weight when there is no vibration at the vibration-assisted penetration depth. The enhancement factor is f, where f is the operating frequency of the downhole variable frequency vibratory impactor. z represents the vibration retention time; z represents the construction depth. For reference depth.
9. The application according to claim 7, characterized in that, The reinforcement coefficient k was determined through on-site calibration before construction. f During construction, in sections with dense cracks, the current construction depth z and the required penetration depth are considered. Calculate the required vibration dwell time using the following formula. : ; By adjusting the operating frequency f and the vibration dwell time t of the downhole variable frequency vibratory impactor v Achieve uniform high-permeability filling throughout the entire pore section.
10. The application according to claim 7, characterized in that, A phased construction and graded material usage strategy was adopted: In the borehole section with a drilling depth of 0~100m, conventional backfill grouting material is used for filling by its own weight. In borehole sections with a drilling depth of 100-200m, the high-flowability self-compacting grouting material described in any one of claims 1-7 is used for backfilling, and the grouting is carried out in conjunction with the downhole variable frequency vibratory compactor assisted grouting method described in claim 8 or 9.